FAKTOR â FAKTOR YANG MEMPENGARUHI KINERJA AUDITOR DI KAP SEMARANG - Mita Septi Anggraeni, 12.05.52.0109; Setyowati, Widhy (Students Journal of Accounting and Banking, 2016)
The study examines the effect of audit structure, the role conflict, the role ambiguity, the understanding of good governance, the independence, emotional intelligence affect the performance of the auditor The method used is the method of convenience sampling. The population in this research is the entire HOOD of the auditor in Semarang city period of 2015. Research data is primary data obtained directly from respondents with a questionnaire. Relationship and (or) influence between variable is described by using multiple regression analysis.Â The results showed that the audit structure and role ambiguity has significant negative effect the performance of the auditor. and the role conflict has no significant negative effect the performance of the auditor. And the understanding of good governance has significant positive effect the performance of the auditor. And the independence of the auditor and emotional intelligence has no significant positive affect on the performance of auditor.Keywords: Audit Sturcture, The Role Conflict, Role Ambiguity, Good Governance, The Independence, Emotional Intelligence, Performance Of Auditor